“МОНГОЛЫН НУУЦ ТОВЧОО”-НЫ НЭГЭН ҮГИЙН ТОВЧ УТГА - Г.Буянтогтох, (Acta Mongolica, 2011)
The Etymology of the word “ NENDE-beat someone to it” of the “Secret History of the Mongols” is such as following :1. Proto Altaic - nen > Manchu - nende; > Mongolian - nenji, gene > genede. 2. Proto Altaic - nen > Mongolian - nen, en.